Malrotation and Fibroblast Growth Factor Receptor-2–Associated Craniosynostosis: An Underrecognized Association and Management Pathway. Issue 1 (18th January 2023) - Harwood, Rachel; O'Shea, Kathryn; Hennedige, Anusha; Parks, Christopher; Turnock, Colette; Wood, Sarah
Abstract : Introduction: Feeding difficulties are common and multifactorial in children with Fibroblast Growth Factor Receptor-2 (FGFR-2) mutations. Intestinal rotation anomalies have been demonstrated to occur more frequently in animals with FGFR-2 mutations. This study aims to describe intestinal rotation anomalies, surgical management, and feeding assistance in children with FGFR-2 mutations who have undergone upper gastrointestinal (UGI) contrast studies. Methods: Retrospective data were collected of children born between 1988 and 2020 in a UK quaternary craniofacial unit with FGFR-2–associated craniosynostosis. A consultant survey of approach to malrotation was undertaken. Results: Thirty-four children were included, 17 (50%) female. Six (18%) had UGI symptoms, which included bilious vomiting (n=2), nonbilious vomiting (n=5), retching (n=1), feed intolerance (n=3), and failure to thrive (n=3). Nine had a gastrostomy in situ. Intestinal rotation anomalies occurred in 4 (12%) children, 3 of whom underwent a Ladd procedure and two third required gastrojejunal feeding postoperatively. Consultants agreed that all children with FGFR-2 mutation and UGI symptoms should undergo UGI contrast study, as should children requiring a gastrostomy. Discussion: Intestinal rotation anomalies in children with FGFR-2 mutations occur more frequently than the general population. Prompt consideration of UGI contrast in symptomatic children with FGFR-2 mutation is recommended to enable early surgical management of children with malrotation.